Concentração da solução nutritiva em sistema fechado com substrato na produção de pontas de estolões de morangueiro e maços de salsa e cebolinha - Schmitt, Odair José (2013)
The aim of this work was to determine criteria for management of nutrient solution in the production of runner tips for producing strawberry plug plants and parsley and chives for commercial mixed bunches. Two experiments were carried out at Departamento de Fitotecnia-UFSM using 2.5 dm3 polypropylene pots filled with sand, placed over 0.8m heigh benches and fertigated by drippers. The first experiment was conducted from 13 October 2011 to 10 April 2012, using strawberry mother plants cv. Camino Real and Oso Grande. Plants were fertigated by five electrical conductivities, 0.4, 0.8, 1.2, 1.6 and 2.0 dS m-1, respectively, in a (5 x 2) completely randomized factorial experimental design. Runner tips emitted by mother plants were collected weekly and counted, being discarded those necrotic. It was determined the number of leaves, crown diameter and dry mass. Runner tips from mother plants of each treatment were rooted in polystyrene trays for plug plants production. Forty five days later, crown diameter, number of expanded leaves and shoot and root dry weight of plug plants were determined. At the end of the experiment, mother plants of each treatment were also collected for dry mass determination of plant organs. The second experiment was conducted from September 12 to October 22, 2012, comparing five electrical conductivities of the nutrient solution, 0.5; 1.5; 2.0; 2.5 and 3.0 dS m-1, respectively, and eight cropping arrays. The arrays were formed by planting side by side in each pot transplants of parsley and chives from one cell of the commercial tray (1S+1C), from two cells of parsley and one of chives (2S+1C), one of parsley and two of chives (1S+2C), two of parsley and two of chives (2S+2C) and four monocropping arrays as controls: seedlings from one cell tray of parsley (1S) and one of chives (1C) and two of parsley (2S) and two of chives (2C) per pot. It was used a (5 x 8) completely randomized factorial experimental design. At the end of the experiment, plants of both species were harvested, separated and fresh (MVPA) and dry mass (MSPA) of shoot were determined. It was concluded that electrical conductivities of the nutritive solution in the range between 0.8 and 1.1 dS m-1 for growing strawberry mother plants lead to higher runner tips and plug plants production. Intercropped parsley and chives can be grown using the same nutrient solution at 2.0 dS m-1 for the commercial production of mixed bunches, while an electrical conductivity of 1.6 dS m-1 can be used for monocropped chives production.